Management staff’s perspectives on intervention strategies for workplace violence prevention in a tertiary health facility in Nigeria: a qualitative study - Agu, Adaoha Pearl; Azuogu, Benedict Ndubueze; Una, Alfred F.; Ituma, Benard; Eze, Irene Ifeyinwa; Onwe, Francis I.; Oka, Onyinyechukwu Uzoamaka; Igwe-Okomiso, Dorathy O.; Agbo, Urudinachi N.; Ewah, Richard; Uneke, Jesse C. (Frontiers in Public Health, 2023)
Introduction: Health workers have increasingly become victims of workplace violence. However, negligible action has been given to developing workplace violence (WPV) prevention programs in hospital settings in low-middle-income countries. An effective workplace violence prevention program is crucial for preventing violence and managing the consequences of incidents. This study assessed management staff perspectives on intervention strategies for workplace violence prevention in a tertiary health facility in Nigeria. Methods: A qualitative study design was employed to explore the intervention strategies for preventing and managing workplace violence at a tertiary health facility in southeast Nigeria. Six focus group discussions were conducted with thirty-eight management-level staff. The interview transcripts were manually coded according to six predefined constructs of workplace violence: creating interdisciplinary harmony and WPV experiences, causes, prevention, program/policy contents, and implementation strategies. A manual thematic analysis approach was adopted, and the results were presented as narratives. Results: The findings revealed recognition, welfare, administrative control, and security as vital strategies for the WPV prevention program. The participants agreed that unanimity among staff could be promoted through respect for all cadres of staff and for people’s perspectives (creating interdisciplinary harmony). Assaults and staff intimidation/victimisation (experiences), attributed to unethical/poor health workers’ behaviour and ethnic discrimination (causes), were viewed as preventable by ensuring patients'/caregivers' welfare through respectful and timely care and staff’s welfare through incentives/remunerations and discouraging intimidation (prevention strategies). Furthermore, the staff expressed that the WPV program should employ administrative controls, including instituting WPV policy/unit, codes of ethics, and standard operating procedures across all workplace facets (program/policy contents), which should be implemented through awareness creation, enforcement of sanctions, and provision of appropriate and adequate security presence in the hospital (policy implementation strategies). Conclusion: Respect, patient/staff welfare, administrative control, and security are strong mechanisms to prevent workplace violence in tertiary hospitals. Hospital management should institutionalize workplace violence prevention programs/policies and ensure compliance.